The Problem of Impartiality in the Framework of Knowledge-Power Relationships of Strategic Research Centers - Çelik, Saadet (Fırat University, 2025)
In this study, highlights the interactions between knowledge and power by examining the functions of strategic research centers in the context of power relations. The study draws attention to the fact that while strategic research centers have become an influential actor in public policy-making thanks to their expertise, they also function as a source of information that serves power structures. In this process, it is demonstrated that those with information are more influential in decision-making processes and are decisive in shaping policies. Strategic research centers make significant contributions to policy-making processes and the production of power by bringing together knowledge and power dynamics. While strategic research centers carry out their activities, their relations with political, economic and social power and power centers raise some evaluations on the objectivity of the information they produce. This situation brings into question how knowledge is produced and used and the concept of objectivity into question. As a matter of fact, these centers have undertaken an indispensable function in the production of power and the direction of policies, but they may also carry the risk of being biased. This study focuses on the effects of strategic research centers on policy-making processes and power production, especially from the perspective of Turkey, and how these effects are shaped in the context of knowledge and power dynamics and the state of bias.

Bu çalışmada stratejik araştırma merkezlerinin iktidar ilişkileri bağlamındaki işlevlerini inceleyerek bilgi ve iktidar arasındaki etkileşimleri vurgular. Çalışma, stratejik araştırma merkezlerinin uzmanlıkları sayesinde kamu politikalarının belirlenmesinde etkili bir aktör haline gelirken aynı zamanda iktidar yapılarına hizmet eden bir bilgi kaynağı olarak da işlev gördüğüne dikkat çeker. Bu süreçte, bilgi sahibi olanların karar alma süreçlerinde daha etkili oldukları ve politikaların şekillenmesinde belirleyici oldukları ortaya konur. Stratejik araştırma merkezleri, bilgi ve iktidar dinamiklerini bir araya getirerek politika yapım süreçlerine ve iktidarın üretimine önemli katkılarda bulunmaktadır. Stratejik araştırma merkezleri faaliyetlerini sürdürürken siyasi, ekonomik ve toplumsal iktidar ve güç odaklarıyla olan ilişkileri, ürettikleri bilginin nesnelliği üzerine bazı değerlendirmeleri gündeme getirmektedir. Bu durum, bilginin nasıl üretildiği ve kullanıldığı konusundaki sorgulamaları ve tarafsızlık anlayışını tartışmaya açmaktadır. Nitekim bu merkezler, iktidarın üretiminde ve politikaların yönlendirilmesinde vazgeçilmez bir işlevi üstlenmiş olduğu gibi taraflı olma riskini de taşıyabilmektedir. Bu çalışma, stratejik araştırma merkezlerinin özellikle Türkiye merceğinden politika yapım süreçlerindeki ve iktidar üretimindeki etkilerini ve bu etkilerin bilgi ve iktidar dinamikleri bağlamında nasıl şekillendiğini ve taraflı olma hali üzerinde durmaktadır.
Stratejik Araştırma Merkezlerinin Bilgi-İktidar İlişkileri Çerçevesinde Tarafsızlık Sorunsalı
Keywords: Politics in International Relations; Uluslararası İlişkilerde Siyaset